2018
DOI: 10.26599/bsa.2018.9050010
|View full text |Cite
|
Sign up to set email alerts
|

A Review of EEG-Based Brain-Computer Interface Systems Design

Abstract: A brain-computer interface (BCI) system can recognize the mental activities pattern by computer algorithms to control the external devices. Electroencephalogram (EEG) is one of the most common used approach for BCI due to the convenience and non-invasive implement. Therefore, more and more BCIs have been designed for the disabled people that suffer from stroke or spinal cord injury to help them for rehabilitation and life. We introduce the common BCI paradigms, the signal processing, and feature extraction met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 79 publications
0
15
0
2
Order By: Relevance
“…According to the situation of drug addicts, the training system of BCI can be used to improve the changes in brain function and can simultaneously help in improving attention and self‐control. Some researchers have reviewed the characteristics and application of the BCI technique, including the EEG signal processing technique, and sports imagination training, such as for stroke, which play a role in rehabilitation [41, 42]. Therefore, BCI is also a potential attempt in drug treatment.…”
Section: Existing Rehabilitation Methods and New Rehabilitation Tecmentioning
confidence: 99%
“…According to the situation of drug addicts, the training system of BCI can be used to improve the changes in brain function and can simultaneously help in improving attention and self‐control. Some researchers have reviewed the characteristics and application of the BCI technique, including the EEG signal processing technique, and sports imagination training, such as for stroke, which play a role in rehabilitation [41, 42]. Therefore, BCI is also a potential attempt in drug treatment.…”
Section: Existing Rehabilitation Methods and New Rehabilitation Tecmentioning
confidence: 99%
“…Removing unrelated channels can improve spatial feature extraction. In time window setting, proper length of the signal segment should be cut out according to the mental activity tasks [18]. Aboalayon et al in their study reported many of the sleep stage detection schemes to employ pre-processing techniques before extracting the features from the signal, such as using frequency-selective-filtering and Discrete Wavelet Transform (DWT).…”
Section: Eeg Signal Processingmentioning
confidence: 99%
“…In this study, we developed a steady state visual evoked potential (SSVEP) triggered brain computer interface (BCI)-functional electrical stimulation (FES) based action observation game featuring a flickering action video for stroke patients who were unable to move their upper limbs. Although it may cause tiredness due to flickering stimuli, a SSVEP-based BCI system has advantages such as no need training and higher classification accuracy compared to a motor-imagery based BCI system [22]. In stroke patients who have difficulties performing motor-imagery, the SSVEP triggering system can be more useful to induce repetitive movement through FES.…”
Section: Introductionmentioning
confidence: 99%